Building the Hindu Kush: monazite records of terrane accretion, plutonism and the evolution of the Himalaya–Karakoram–Tibet orogen. (14th June 2014) - Faisal, Shah; Larson, Kyle P.; Cottle, John M.; Lamming, Jaida
Abstract In situ U‐Th/Pb (LA‐ICP‐MS) monazite ages from the Hindu Kush of NW Pakistan provide new petrochronologic constraints on the tectonic evolution of the Himalaya–Karakoram–Tibet orogen. Monazites from two adjacent garnet + staurolite schist specimens yield multiple age populations that record the major Mesozoic and Cenozoic deformational, magmatic and metamorphic events along the southern margin of Eurasia. These include the accretion of the Hindu Kush–SW Pamir to Eurasia during the Late Triassic, followed by the accretion of the Karakoram terrane in the Early Jurassic. Younger Jurassic and Cretaceous ages record the development of an Andean‐style volcanic arc along the southern Eurasian margin, which ended with the docking of the Kohistan island arc and the emplacement of the Kohistan–Ladakh batholith during the Late Cretaceous. The initial Eocene collision of India with Eurasia was followed by widespread high‐temperature metamorphism and anatexis associated with crustal thickening within the Himalaya system in the Late Oligocene and Early Miocene.